2020
DOI: 10.1002/cbl.30483
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in access to education: Lessons from the COVID‐19 pandemic

Abstract: The COVID‐19 pandemic has brought attention to the stark inequities in public education worldwide, with the United Nations sharing these statistics: Schools closed in 191 countries, affecting 1.5 billion students and 63 million primary and secondary school teachers. Half of students did not have access to a computer, and 40% did not have internet access. A total of 56 million children live in areas that are not served by mobile networks — for example, in sub‐Saharan Africa. In the United States, about 7 millio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…For example, 56 million children in sub-Saharan African countries experience digital inequality, as the mobile networks do not provide adequate service and experience problems every day. Even in many developed countries, it is stated that millions of school-age students live in homes without Internet service [21][22][23][24][25][26]. In this context, the results of the research conducted by Jaeger and Blaabaek [27] also revealed that COVID-19 has further increased the inequality in learning opportunities and that families with better socioeconomic status are more advantaged than financially more impoverished families during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, 56 million children in sub-Saharan African countries experience digital inequality, as the mobile networks do not provide adequate service and experience problems every day. Even in many developed countries, it is stated that millions of school-age students live in homes without Internet service [21][22][23][24][25][26]. In this context, the results of the research conducted by Jaeger and Blaabaek [27] also revealed that COVID-19 has further increased the inequality in learning opportunities and that families with better socioeconomic status are more advantaged than financially more impoverished families during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mitchell (2020) reports that students are missing more days of school more easily, which contributes to chronic absenteeism. Xie et al (2020) also discuss drawbacks of online learning. They highlight network instability and technological constraints, a lack of a sense of belonging and connectedness, the presence of distractions, and a lack of engagement as major drawbacks.…”
Section: The Challenges Of Remote Learningmentioning
confidence: 98%
“…Additionally, while school closures and the last-minute shift to distance, remote, or hybrid learning has been linked to severely slowing the spread of the coronavirus to school aged children, teachers, and their families,4 the closures also accelerated the "digital transformation" of schooling. Planning wise, school closures and the "digital transformation" of schooling happened without much notice, expertise, or preparedness, at the school level (Iivari et al, 2020, p. 2;Walters, 2020). According to Greenberg (2020), school culture and experience with technology were the strongest predictors of a successful transition to remote learning at 50 schools in a California nonprofit portfolio.5 Digital tools became more than in-person learning add-ons.…”
Section: The Challenges Of Remote Learningmentioning
confidence: 99%
See 2 more Smart Citations